2020
DOI: 10.1159/000508726
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of HATCH Score and Coronary Artery Disease Complexity on Atrial Fibrillation after On-Pump Coronary Artery Bypass Graft Surgery

Abstract: Objective: Postoperative atrial fibrillation (PoAF) is the most frequently encountered rhythm problem after coronary artery bypass graft (CABG) surgery. This situation decreases the capacity of the patients with respect to functional exercise and creates a risk for stroke. In this study, we aimed to determine the effect of coronary artery disease extensiveness and HATCH score on PoAF in patients undergoing CABG surgery with cardiopulmonary bypass. Subjects and Methods: Patients who underwent CABG between Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
1
16
4
1
Order By: Relevance
“…A total of 352 patients were included in the study conducted by Engin et al, in 2020, in which the relationship between HATCH score and PoAF was investigated, and PoAF was found to develop in 26.7% of the patients. In the multivariate analysis, HATCH scores>2 (OR: 1.022, 95% CI: 1.004–1.128, p = 0.032) were determined as independent predictors for PoAF [ 4 ]. The main limitation of these three studies is their retrospective design.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 352 patients were included in the study conducted by Engin et al, in 2020, in which the relationship between HATCH score and PoAF was investigated, and PoAF was found to develop in 26.7% of the patients. In the multivariate analysis, HATCH scores>2 (OR: 1.022, 95% CI: 1.004–1.128, p = 0.032) were determined as independent predictors for PoAF [ 4 ]. The main limitation of these three studies is their retrospective design.…”
Section: Discussionmentioning
confidence: 99%
“…This scoring system includes the preoperative data of the patients. Scoring according to the characteristics of the patients was made as follows [ 4 ]:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim here is to reveal a more HATCH score and POAF score. 14,15 However, Ozsin et al 16 reported SYNTAX score II was not an independent predictor for the development of PoAF but they observed that higher SYNTAX score II was correlated with the development of PoAF.…”
Section: One Of the Most Important Problems In Studies Investigatingmentioning
confidence: 99%
“…The aim here is to reveal a more predictive factor for PoAF by assigning various scores to known risk factors according to their potency. The most commonly used ones are CHA2DS2‐VASc (Congestive heart failure, Hypertension Age [≥65 = 1 point, ≥75 = 2 points], Diabetes, and Stroke/transient ischemic attack (2 points)—vascular disease [peripheral arterial disease, previous myocardial infarction, aortic atheroma]) score, HATCH score and POAF score 14,15 . However, Ozsin et al 16 reported SYNTAX score II was not an independent predictor for the development of PoAF but they observed that higher SYNTAX score II was correlated with the development of PoAF.…”
mentioning
confidence: 99%